2020
DOI: 10.1016/j.forsciint.2020.110304
|View full text |Cite
|
Sign up to set email alerts
|

Purity estimation of seized stimulant-type new psychoactive substances without reference standards by nitrogen chemiluminescence detection combined with GC-APCI-QTOFMS

Abstract: Purity estimation of seized stimulant-type new psychoactive substances without reference standards by nitrogen chemiluminescence detection combined with GC-APCI-QTOFMS Samuel Mesihää (Conceptualization) (Formal analysis) (Methodology) (Writing -original draft), Ilpo Rasanen (Methodology), Ilkka Ojanperä (Conceptualization) (Supervision) (Writing -review and editing)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The characterization of indatraline revealed an unexpectedly low concentration of the main compound. While other studies that investigated seized products reported powder purities between 20 and 100%, their mean determined purity was 48.6% or 81% [23,24].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The characterization of indatraline revealed an unexpectedly low concentration of the main compound. While other studies that investigated seized products reported powder purities between 20 and 100%, their mean determined purity was 48.6% or 81% [23,24].…”
Section: Discussionmentioning
confidence: 83%
“…The characterization of indatraline revealed an unexpectedly low concentration of the main compound. While other studies that investigated seized products reported powder purities between 20 and 100%, their mean determined purity was 48.6% or 81% [ 23 , 24 ]. Especially, the considerable amount of ammonium acetate in the indatraline drug product was, to our knowledge, not described before.…”
Section: Discussionmentioning
confidence: 99%
“…2019 application of 2D-LC for the separation of isomeric and structurally related complex mixtures of NPS [ 948 ]; analysis of 1357 narcotics confiscated by the police identified eighteen members of synthetic cannabinoid group, six cathinone compounds, three different tryptamine compounds, and two compounds from the phenethylamine group [ 949 ]; analysis of 70 doses of blotter papers coming from forensic cases, identified mixtures of drugs, such as DOB, 25I–NBOMe, MDMA and 25I–NBOMe imine were identified using CG-MS [ 950 ]; Raman spectroscopy and surface-enhanced Raman scattering (SERS) combined with chemometrics approaches, for rapid and portable quantitative detection and discrimination of a wide range of novel psychoactive substances (methcathinone and aminoindane derivatives) [ 951 ]; Raman spectroscopy for the identification and classification of seized Customs samples into three NPS families. [ 952 ]; 2020 low-voltage paper spray ionization coupled with QTOF-MS method was developed and employed for the qualitative analysis of NPS in street drug blotter samples [ 953 ]; GC-MS analysis to evaluate the presence, chemical composition and profile of NPS in blotters seized in the State of Santa Catarina, Brazil, over the period of 2011–2017 [ 954 ]; analytical strategies and MS instruments used for the analysis of NPS compounds [ 955 ]; novel application of the atmospheric solids analysis probe (ASAP) using medical swabs has coupled to a triple quadrupole mass analyzer under a data-dependent acquisition mode to perform a suspect screening of NPS in different types of samples as well as on surfaces [ 956 ]; determination of the chiral status of fifty-one chiral different NPS purchased from online vendors via the Internet [ 957 ]; an enantioselective HPLC-UV method with applicability to a broad spectrum of NPS [ 958 ]; derivatization for GC-MS-based NPS identification [ 959 ]; IR of 301 new psychoactive substances (NPS) reference substances, including 100 synthetic cannabinoids, 81 synthetic cathinone, 42 phenethylamines, 9 tryptamines, 5 piperazines, 7 phencyclidine-type substances, 2 aminoindanes, 55 other types were analyzed [ 960 ]; review of currently available analytical methodologies for the identification and quantification of NPS [ 961 ]; GC-NCD-APCI-QTOFMS method for fast quantitative estimation of stimulant-type NPS [ 962 ]; quantitative H-1 NMR (H-1-qNMR) method for quantification of twelve NPS is seized samples [ 963 ]; analysis of tap water for investigation of 23 psychoactive substances [ 964 ]; analysis of samples using HPLC-DAD and SFC-MS/MS for detection of NPS in biological and seized samples [ 965 ]; quantitative analysis of NPSs by IR including the IR spectra of 301 NPS reference substances (100 synthetic cannabinoids, 81 synthetic cathinone, 42 phenethylamines, 9 tryptamines, 5 piperazines, 7 phencyclidine-type substances, 2 aminoindanes, 55 other types) [ 960 ]; UHPLC-QTOF-MS method used with an online mass spectral database (…”
Section: Instrument Focusmentioning
confidence: 99%
“…GC‐IR was also used in the differentiation between two analogues of MDPV (Abiedalla et al, 2017). Another type of GC technique recently reported is GC with nitrogen chemiluminescence detection coupled QTOF mass spectrometry (GC‐NCD‐QTOF‐MS), using to atmospheric pressure chemical ionization (Mesihää et al, 2020). A method using secondary reference materials was applied to the analysis of several stimulants, including cathinones in seized materials, and exhibited the capacity to estimate the purity of the drug (Mesihää et al, 2020).…”
Section: Emerging Techniquesmentioning
confidence: 99%
“…Another type of GC technique recently reported is GC with nitrogen chemiluminescence detection coupled QTOF mass spectrometry (GC‐NCD‐QTOF‐MS), using to atmospheric pressure chemical ionization (Mesihää et al, 2020). A method using secondary reference materials was applied to the analysis of several stimulants, including cathinones in seized materials, and exhibited the capacity to estimate the purity of the drug (Mesihää et al, 2020). One additional limitation to GC‐IR is reference libraries (like for GC‐MS) do not exist so laboratories may not be able to search their unknown IR spectra against other known drugs or NPS.…”
Section: Emerging Techniquesmentioning
confidence: 99%